Podcast production standards in light of creative media content: A survey study on a sample of academic and professional experts in media and communication in Riyadh, Kingdom of Saudi Arabia (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to identify the applications and techniques of producing "podcast" programs, determine the performance measurement and indicators of "podcast" production, identify the diversity of visual media content (video - audio) in the Saudi "podcast", and establish standards for "podcast" production in light of the media content. The creative method was used, and the analytical descriptive approach was used, and the study tool was the questionnaire, while the study community consisted of a sample of academic and professional experts in media and communication in Riyadh, numbering (250) female employees., and is estimated at a percentage of (5.9), and their percentage reached (821) from the study community, and the most prominent findings of the study are as follows: The average responses of the study community members towards the creative criteria through which “podcast” programs are produced from The academic and professional experts in media and communication in Riyadh came with an arithmetic average of (4), and a relative weight of 80%. With an arithmetic mean of (4.04), and a relative weight of 81%, and that the average responses of the members of the study community towards the applications and techniques of producing "podcast" programs from the point of view of academic and professional experts in media and communication in Riyadh, came with an arithmetic mean of (4.1), and a relative weight of 82%, and that The average responses of the members of the study community towards methods of measuring the performance and production indicators of the "podcast" programs from the point of view of academic and professional experts in media and communication in Riyadh came with an arithmetic mean of (4.2), and a relative weight of 85%, and that the average responses of the members of the study community towards the most prominent Saudi "podcast" programs In terms of content diversity from the point of view of academic and professional experts in media and communication in Riyadh, it came with an arithmetic mean of (3.6), and a relative weight of 72%.Recommendations: The need to pay attention to the use of podcast technology in developing listening skills, and to pay attention to studying the presence of Saudi podcast programs that talk about the Kingdom's projects globally, which reflects the existence of soft power externally, and the need to employ podcast technology in all educational stages and subjects because of its impact on increasing the effectiveness of learning from During academic achievement, and the need to increase modern technological techniques in the production of Saudi podcast programs and interest in publishing them in media circles, and the importance of training male and female teachers by producing and designing podcast files and employing them in the educational process, and workshops should be held for young people and workers in the field of podcasts on the importance of using it and ways to operate it and benefit from it in developing skills And giving the development of podcast programs great importance as a Saudi media industry that leads the media in the world, and the importance of applying creative standards in media production in the Kingdom of Saudi Arabia, which leads to creative productions that represent the Kingdom.
Keywords: Media; Communication; Podcast; Media Content; Saudi Arabia